Introduction of Basic Accounting Concepts in Kalam Kudus Senior High School Pekanbaru - Wati, Yenny (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
This activity aims to provide students with understanding, knowledge, and an assessment of their abilities in basic accounting concepts. This activity uses lectures, questions and answers, practice and quizzes, and the distribution of questionnaires to gather feedback and suggestions from students. On Monday, August 1st, 2022, this activity was completed offline. The Kalam Kudus Senior High School Pekanbaru students who took part in this activity numbered 14 in total. According to the results of the assessment of student abilities through the provision of accounting practicum questions and quizzes, 90 percent of students can understand, answer, and solve accounting practicum questions and quizzes well. The evaluation of the introduction of basic accounting concepts concluded that it went smoothly and left a positive impression on the students of Kalam Kudus Senior High School Pekanbaru. This activity is intended to stimulate students’ interest in the field of accounting.